Multiprobe estimation of field line curvature radius in the equatorial magnetosphere and the use of proton precipitations in magnetosphere‐ionosphere mapping. Issue 8 (9th August 2013) - Liang, Jun; Donovan, E.; Spanswick, E.; Angelopoulos, V.
Abstract : [1] Nonadiabatic, chaotic motion of ions under a curved geomagnetic field geometry is well recognized as a key mechanism that leads to the pitch angle scattering of protons in the equatorial magnetosphere. The efficiency of such proton pitch angle scattering process is energy dependent and controlled by the radius of curvature of the magnetic field line (RCMFL). The protons scattered into the loss cone will precipitate into the ionosphere and excite proton auroras there. In this study, we propose techniques to calculate the RCMFL based upon multiprobe measurements under different probe geometries. We also demonstrate how to use the obtained RCMFL to evaluate the proton precipitation fluxes, and further use the proton precipitation features to help estimate the magnetosphere‐ionosphere mapping. Our procedures are summarized as follows: (1) We calculate the RCMFL using Time History of Events and Macroscale Interactions during Substorms (THEMIS) multiprobe measurements. (2) With the obtained RCMFL, we evaluate the scattering efficiency and in turn the loss cone fluxes of the magnetospheric protons at different energy levels. (3) The above evaluation of the in situ loss cone fluxes is compared to the ionospheric measurements of proton precipitation fluxes in various energy ranges and/or the optical proton auroras to estimate the possible footprint of THEMIS probes in the ionosphere. Key Points: we propose techniques to calculate the field line curvature radius We demonstrate the techniques in three THEMIS events We demonstrate the use the proton precipitation to estimate M‐I mapping